Clinical outcomes and bone‐level alterations around one‐piece mini dental implants retaining mandibular overdentures: 5‐year follow‐up of a prospective cohort study. Issue 6 (9th March 2020) - Enkling, Norbert; Moazzin, Rim; Geers, Gregor; Kokoschka, Stephanie; Abou‐Ayash, Samir; Schimmel, Martin
Abstract: Objectives: To report on the clinical outcomes of one‐piece mini dental implants (MDIs) retaining mandibular implant overdentures (IODs), including marginal bone‐level alterations (ΔMBLs), clinical peri‐implant parameters, and technical‐ and biological complications during a 5‐year follow‐up. The null hypothesis was that ΔMBLs would be equal in subjects older than 65 years relative to younger subjects. Materials and methods: Four 1.8‐mm diameter one‐piece MDIs with ball attachments were placed in the interforaminal region of 20 edentulous subjects. The existing complete dentures were converted to IODs. Standardized radiographs of each implant were taken at implant placement (baseline) and during the five‐year follow‐up. ΔMBLs and potential influencing factors were evaluated, and peri‐implant parameters, and biological and technical complications were recorded. Results: The implant and prosthetic survival rates were both 100%. IODs fractured in seven participants. The overall mean ΔMBL after 5 years was −1.18 mm (standard deviation: 0.79 mm). ΔMBLs per month were most pronounced within the first 3 months after implant placement. ΔMBLs were not influenced by the implant location, the presence of keratinized mucosa, or gender. However, ΔMBLs were significantly smaller in subjects older than 65 years ( p = .007). Conclusions: One‐piece MDIs retaining mandibular IODs with O‐ring attachments are a predictable treatment option, providing stable peri‐implant bone and soft tissue conditions over a mid‐term follow‐up. Incorporating a metal reinforcement can prevent denture fracturing when converting a complete denture into an IOD. The presence of keratinized mucosa does not necessarily lead to decreased bone‐level changes. Advanced age might be beneficial in terms of peri‐implant bone stability.